Integration of an Addiction Team in a Liver Transplantation Center. Issue 11 (11th October 2019) - Donnadieu‐Rigole, Hélène; Jaubert, Laura; Ursic‐Bedoya, José; Hanslik, Bertrand; Mura, Thibault; Gamon, Lucie; Faure, Stéphanie; Navarro, Francis; Perney, Pascal; Herrero, Astrid; Pageaux, Georges‐Philippe
Abstract : Up to 50% of liver transplantation (LT) recipients with known or clandestine alcohol‐use disorder (AUD) before surgery return to alcohol use after LT. However, only severe alcohol relapse, which varies in frequency from 11% to 26% of patients, has an impact on longterm survival and significantly decreases survival rates after 10 years. Therefore, it is crucial to identify patients with the highest risk of severe relapse in order to arrange specific, standardized monitoring by an addiction team before and after LT. The aims of this study were to describe the effects of combined management of AUD on the rate of severe alcohol relapse and to determine the risk factors before LT that predict severe relapse. Patients transplanted between January 2008 and December 2014 who had met with the LT team's addiction specialist were included in the study. Patients who exhibited alcohol‐related relapse risk factors received specific addiction follow‐up. A total of 235 patients were enrolled in the study. Most of them were men (79%), and the mean age at the time of the LT was 55.7 years. Severe relapse occurred in only 9% of the transplant recipients. Alcohol‐related factors of severe relapse were a pretransplant abstinence of 6 months and family, legal, or professional consequences of alcohol consumption, whereas the nonalcohol‐related factors were being single and being eligible for a disability pension. In conclusion, the integration of an addiction team in a LT center may be beneficial. The addiction specialist can identify patients at risk of severe relapse in the pretransplantation period and hence arrange for specific follow‐up.